An Industrial quality control on Selecta Wall's Inc. - Batungbakal, Pia Marie S. (College of Engineering, 2004)
An industrial quality control study was conducted on Selecta-Wall's Inc. with an aim to evaluate their current quality system and sampling plan. The group focused on the Cornetto line of products, which constitute the second largest share in the production of Selecta-Wall's, Inc. next to bulk ice cream. The researchers conducted plant visits and interviews of key personnel in order to familiarize with the production and quality systems. Historical data were obtained to facilitate a comprehensive analysis of the current processes. Critical points in the system which set off variations in the quality of the finished goods were looked into. Historical data on valid customer complaints from 1995 to 2003 show that inconsistencies in the amount of mouthfills and ripple, incompletely filled cups or cones, and off taste are among the top customer complaints relating to product quality. Thus, the group performed an analysis on the gross weight of the finished product and process yield as these best approximate the uniformity of the finished goods. These are the bases for the construction and analysis of control charts and process capability studies. Results of the statistical process control and process capability analyses show that the current manufacturing process is statistically out of control and below the industry standards for process capability. Adjustments were made to discard out of control points with assignable causes and new control limits were determined. The actual process capabilities are : 0.25 for Choco Java (cups), 0.1015 for Cookies 'n' Cream (cups) and 0.1149 for Mango Cheesecake (cups). These figures all substantiate the need for improvements in the current processes of the company. Recommendations for the improvement of the system have been generated. These are implementation of regular check-up of machines at the start of each day, training of operators on troubleshooting and detection of machine malfunction, routine checks for machine precision on the amount of inclusions dispensed, strict monitoring of operators for compliance with machine calibration, improve record-keeping system to ensure accuracy and credibility of data, and plotting of data points to allow easier detection of patterns on the parameters measured. The group recommends a sampling that can better determine the true acceptance level of the batch. A normal variables sampling plan at normal inspection level, a lot-by-lot variables acceptance sampling plan (MIL STD 414), and a lot-by-lot attributes acceptance sampling plan are recommended for the raw materials, work-in-process, and finished goods, respectively. Further analysis of other quality characteristics that can provide a more direct view of the products' quality such as microbiological count, fat content, pH level, and moisture content are recommended to supplement this study.